Increased Perinatal Morbidity and Mortality Among Asian American and Pacific Islander Women in the United States. (March 2017) - Siddiqui, Maryam; Minhaj, Mohammed; Mueller, Ariel; Tung, Avery; Scavone, Barbara; Rana, Sarosh; Shahul, Sajid
Abstract : BACKGROUND: Asian American/Pacific Islanders (AAPIs) are the fastest-growing racial group in the United States. Despite a higher socioeconomic status, AAPI women experience higher rates of maternal morbidity and mortality. METHODS: Using the National Inpatient Sample, we performed a retrospective cohort analysis of women who were hospitalized for delivery from 2002 to 2013. The primary outcome variable was inpatient mortality rate, and the presence of severe maternal morbidities was estimated using the Bateman Comorbidity Index, a validated tool for predicting obstetric morbidity. RESULTS: AAPI women presenting for delivery between 2003 and 2012 were older, more likely to reside in a zip code in the top quartile of annual income, be privately insured than Caucasian women, and less likely to have a higher Bateman Comorbidity Index. However, AAPI women had a higher likelihood of postpartum hemorrhage (3.4% vs 2.7%, P < .001), uterine atony, severe perineal lacerations, and severe maternal morbidities. Procedures such as transfusion, hysterectomy, and mechanical ventilation were also more common in AAPI women. Furthermore, AAPI women had a higher mortality rate that persisted despite adjustment for an apparently higher income and comorbidities (odds ratio 1.72, 95% confidence interval: 1.14–2.59, P = .01). CONCLUSIONS: Despite having a higher socioeconomic status, AAPI women had higher rates of maternal mortality during hospitalization for delivery. This increase persisted even after adjustment for factors known to affect peripartum outcomes. Further investigation is needed to better clarify the causes of racial differences in maternal morbidity and mortality. Abstract : Supplemental Digital Content is available in the text.